1996
DOI: 10.1104/pp.110.1.23
|View full text |Cite
|
Sign up to set email alerts
|

A Viral Movement Protein as a Nuclear Shuttle (The Geminivirus BR1 Movement Protein Contains Domains Essential for Interaction with BL1 and Nuclear Localization)

Abstract: For the nuclear replicating bipartite geminiviruses such as squash leaf curl to systemically infect the host requires the active participation of two virus-encoded movement proteins, BR1 and BL1. These act in a cooperative manner to transport the viral singlestranded DNA genome from its site of replication in the nucleus to the cell periphery (A.A. Sanderfoot, S.C. Lazarowitz [1995] Plant Cell 7: 1185-1194). We have proposed that BR1 functions as a nuclear shuttle protein, transporting the viral single-strande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
0
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(116 citation statements)
references
References 52 publications
(97 reference statements)
3
109
0
2
Order By: Relevance
“…To facilitate the quantitative measurement of proteolytic rates, we fused the first 111 amino acids of IAA17 (Figure 1), which includes all residues N-terminal to conserved domain III, to nuclear-targeted LUC (LUC:NLS). Although amino acids shown to function as a bipartite nuclear localization signal (NLS) in Arabidopsis IAA3 and IAA9 and pea IAA4 are present in IAA17(1-111), an exogenous squash leaf curl virus NLS (Sanderfoot et al, 1996;Worley et al, 2000) was included to try to ensure the proper subcellular localization of the wild-type and mutant LUC fusion proteins. IAA17 (1-111):LUC:NLS showed a rapid rate of degradation under basal conditions of ;10 min ( Figure 2A) in a cycloheximidebased degradation assay (Worley et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…To facilitate the quantitative measurement of proteolytic rates, we fused the first 111 amino acids of IAA17 (Figure 1), which includes all residues N-terminal to conserved domain III, to nuclear-targeted LUC (LUC:NLS). Although amino acids shown to function as a bipartite nuclear localization signal (NLS) in Arabidopsis IAA3 and IAA9 and pea IAA4 are present in IAA17(1-111), an exogenous squash leaf curl virus NLS (Sanderfoot et al, 1996;Worley et al, 2000) was included to try to ensure the proper subcellular localization of the wild-type and mutant LUC fusion proteins. IAA17 (1-111):LUC:NLS showed a rapid rate of degradation under basal conditions of ;10 min ( Figure 2A) in a cycloheximidebased degradation assay (Worley et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Bipartite geminiviruses have been shown to encode a specific nonstructural protein, BR1, that shuttles the viral genome into and out of the nucleus (Noueiry et al, 1994 ;Sanderfoot & Lazarowitz, 1995 ;Sanderfoot et al, 1996). Since TYLCV, a monopartite geminivirus, lacks BR1, another viral protein must mediate nuclear transport of the TYLCV genome.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike most other plant viruses, both mono-and bipartite geminiviruses need to be imported into the host-plant cell nucleus for their replication (Timmermans et al, 1994). Studies of the bipartite geminivirus squash leaf curl virus (SqLCV) indicated that a protein (BR1) encoded by the DNA B component binds the genomic viral ssDNA and shuttles it into and out of the host cell nucleus (Sanderfoot & Lazarowitz, 1995 ;Sanderfoot et al, 1996). Also, Noueiry et al (1994) have shown that the BR1 protein of another bipartite geminivirus, bean dwarf mosaic geminivirus (BDMV), is involved in the nuclear export of viral DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Integration may induce small ssDNA; nuclear shuttle, cell-to-cell movement (Pascal et al, 1994;Sanderfoot and Lazarowitz, (SqLCV) 1995;Sanderfoot et al, 1996) Cucumber mosaic virus (CMV) 3a ssRNA, ssDNA; cell-to-cell movement (Ding et al, 1995;Li and Palukaitis, 1996 HC-Pro ssRNA (Maia and Bernardi, 1996) *Additional movement proteins with SSB activity are described in Mushegian and Koonin (1993), Carrington et al (1996), and Lazarowitz and Beachy (1999). deletions, less than 100 bp, of plant DNA at the insertion site. In addition, integration also generates`®ller' DNA, less than 50 bp homologous to nearby plant DNA, at the T-DNA-plant junction.…”
Section: Integration (Table 1 Item 11)mentioning
confidence: 99%